Peripheral Adenomatoid Odontogenic Tumor — A Rare Cause of Gingival Enlargement: A Case Report with CBCT Findings - Sadasivan A; Ramesh R; Kurien NM (Dove Medical Press, 2020)
Arun Sadasivan,1 Roshni Ramesh,2 Nikhil M Kurien3 1Department of Periodontics, Sree Mookambika Institute of Dental Sciences, Kulashekaram, Tamil Nadu, India; 2Department of Periodontics, Government Dental College, Thrissur, Kerala, India; 3Department of Oral and Maxillofacial Surgery, PMS College of Dental Science and Research, Trivandrum, Kerala, IndiaCorrespondence: Arun SadasivanDepartment of Periodontics, Sree Mookambika Institute of Dental Sciences, Kulashekaram, Tamil Nadu, IndiaTel +91 9847246961Email sadasivan_arun@hotmail.comIntroduction: Adenomatoid odontogenic tumor (AOT) is an uncommon benign odontogenic lesion with varied clinical and histological presentation. It has slow growth potential and a low recurrence rate. The tumor is mainly seen in females in the second decade of life, predominantly affecting the maxilla and associated most often with unerupted canine teeth, earning the epithet “two-thirds tumor”. There are three variants: intrafollicular, extrafollicular, and peripheral. The peripheral or extra osseous type is a rare form that arises in gingival tissue.Case Presentation: This article describes a case of AOT in a 10-year-old girl who presented with gingival enlargement in relation to the maxillary left central incisor. Interestingly, intraoral periapical radiography did not show any significant findings. However, cone-beam computed tomography of the site revealed significant bone loss in the area. A surgical excision was done. Histopathological examination revealed features of AOT. Based on clinical, radiographic, and histological evidence, a diagnosis of peripheral AOT (PAOT) was made.Conclusion: PAOT is a rare disease entity in children that mimics gingival swelling, and may often be misdiagnosed by dentists. With literature still ambiguous on the origin of the tumor and biological course, it becomes imperative to examine any gingival swelling in children with a proper clinical examination, periapical radiography, and if necessary cone-beam computed tomography. Excision and histopathological evaluation will help in confirming the exact disease condition.Keywords: peripheral adenomatoid odontogenic tumour, gingival enlargement, maxillary, CBCT